Tantangan dan Solusi dalam Pembentukan Karakter Pendidikan Agama Kristen Anak di Era Digital - Delima Hot Marito Hasugian; Ordekoria Saragih (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2025)
Character formation of children in Christian religious education faces new challenges in the digital era. This journal discusses the challenges and solutions in character formation of children in the digital era. This study uses a qualitative method with a literature review (library research). The results of the study indicate that there are challenges that must be faced when education is faced with the era of technology that is increasingly developing rapidly. However, if the use of technology is wise, parental supervision, and effective religious education can help shape strong children's characters and this is a very good solution to help the development of students, especially in the scope of Christian Religious Education.